Child related policy and legislative reforms in Malaysia - Kahar, Rojanah; Mohd Zin, Najibah (Institut Sosial Malaysia & Faculty of Human Ecology, UPM, 2011)
This paper examines the existed child related policies and child welfare laws in Malaysia with regards to children's rights with special concern to the implementation of diverse child related policies which affect child best interest in the Malaysian context after the ratification of United Nation Convention on Rights of a Child (UNCRC) in 1995. Content analysis of secondary data has been utilized in order to understand the implementation of diverse policies and laws within the purview of family law development and other related areas that affect child best interests. This study established that diverse social policies and numerous child related legislations addresses and accommodated the best interest for children both for Muslim and non Muslim since both groups had different laws. Nonetheless, the absence of child-focused policy in Malaysia affects the smooth implementation of policies and laws which relates to the best interest of children. Thus, child-focused policy is important to protect children's best interest in all areas including family law. Therefore it is anticipated that the introduction of National Child Policy and National Child Protection Policy in 2009 would bring positive changes to the Malaysian children.